Mission Planning Tool for space debris studies with the MeerKAT radar - Dhondea, Ashiv Rao (Department of Electrical Engineering, 2019)
The Radar Remote Sensing Group at the University of Cape Town is currently investigating the feasibility of building an active radar system employing the MeerKAT radio telescope as receiver for space debris detection, tracking and imaging. This dissertation details the development of a Mission Planning Tool (MPT) to perform sensor scheduling and to support the performance prediction and analysis of the proposed MeerKAT radar. The MeerKAT radar project proposal is made in the context of developing space surveillance and tracking capacities in South Africa. The MeerKAT radar is intended to operate bistatically, with a transmitter located in Bredasdorp (South Africa) and the MeerKAT radio telescope as receiver. The system design and radar signal processing design are currently under development in another RRSG project. Before the feasibility study can progress further, a Mission Planning Tool has been developed to assist in scheduling the bistatic radar to perform an observation experiment, to calculate the predicted radar measurements and errors as well as to estimate the orbit of the observed object. This report documents how these objectives were met by the MPT software developed in Python. Given a LEO space object of interest’s Two Line Element set, the MPT performs orbit propagation with an SGP4 method to generate trajectories for radar performance evaluation. The MPT determines the most opportune epoch (the longest possible target dwell-time within the antenna beam) for executing an observation experiment with the MeerKAT radar. Space objects investigated in this project were found to be have spent between 4.5 s to 12.8 s in the transmitter’s illuminating beam. The MeerKAT radio telescopes are tasked to act as receivers at the appropriate antenna pointing and time period. Based on the bistatic geometry of the specific observation experiment, the MPT predicts the signal-to-noise ratio at the radar receiver as well as the bistatic range, bistatic Doppler shift and look angles. The integrated SNR values for the experiments considered in this report ranged from 11 dB to 68 dB. From the coherently integrated SNR, the MPT estimates the radar measurement errors. Finally, the orbit determination module was engineered with two radar measurement schemes: a bistatic range and Doppler shift scheme and a bistatic range and look angles scheme. Monte Carlo experiments were run to evaluate the tracking performance resulting from the two tracking schemes. The Gauss-Newton tracking filter based on the first scheme fails to converge whereas it produces accurate results with the second scheme (estimated position error of 2 m and velocity error of 0.08 m/s). It is therefore recommended to opt for the bistatic range and look angles measurement scheme in future work. Since the current MeerKAT radar design cannot create look angles measurements, an observables estimation scheme was adopted. It was found that this scheme produced accurate elevation and azimuth angles with an estimation error of ±0.04◦ . Since the quoted values result from a preliminary design of the MeerKAT radar, they are bound to change in the final design. Therefore the MPT should be loaded with the final radar design’s parameters and run again to produce useful results. This reports shows that, with the help of the Mission Planning Tool developed in this project, the proposed MeerKAT radar can be feasibly scheduled to observe and track space objects in the LEO regime based on a single target pass.